The Effect of Nanocrystalline Cellulose (NCC) Filler on Polylactic Acid (PLA) Nanocomposite Properties - Simangunsong, Daniel I.; Hutapea, Try H. A.; Lee, Hyung Woo; Ahn, Jung Oh; Sitompul, Johnner (Journal of Engineering and Technological Sciences, 2018)
This paper discusses the effect of nanocrystalline cellulose (NCC) when used as filler on polylactic acid (PLA)-based nanocomposites and on its mechanical properties and permeability. NCC was produced from commercial cellulose and another cellulose source, i.e. oil palm empty fruit bunch, by hydrolysis of microcrystalline cellulose with sulphuric acid and by oxidation with ammonium persulfate. The nanocomposites were made by adding nanocrystalline cellulose with varying compositions into PLA. A solvent casting method was used to produce a nanocomposite film with 5% v/v triacetin as a coupling agent. Both methods produced crystalline celluloses within the micro and nano range with mean particle size at 99.5 nm and 157.9 nm for the sulphuric acid hydrolysis and the ammonium persulfate oxidation method, respectively. The utilization of NCC as PLA composite filler increased the percentage of elongation at break with a highest percentage 19.02% for addition of 1% NCC filler. However, higher compositions of cellulosic filler resulted in a decreasing trend of tensile strength and elongation at break. Higher content of NCC filler in the PLA matrix increased the nanocompositeâs water vapor permeability.